Work engagement, emotional exhaustion, and OCB-civic virtue among nurses: a multilevel analysis of emotional supervisor support - Pohl, Sabine; Djediat, Abdel; Van der Linden, Jan; Closon, Caroline; Galletta, Maura (Frontiers in Psychology, 2023)
This study investigates the moderating role of supervisor emotional support at the group level on the relationship between emotional exhaustion and work engagement with organizational citizenship behavior-civic virtue (OCB-civic virtue) at the individual level among nurses. A cross-sectional study was carried out on 558 nurses, who were nested in 36 working units from two hospitals in Algiers. Multilevel analysis using Hierarchical Linear Modeling was performed. Results indicate that the positive effect of work engagement on OCB-civic virtue is moderated by supervisor emotional support at group level. The negative relationship between nurses' emotional exhaustion and OCB-civic virtue at the individual level is buffered by supervisor emotional support at the group level. In consequence, supervisor emotional support experienced by the team has an influence on the emotional exhaustion and work engagement -OCB-civic virtue relationships.